2019
DOI: 10.1080/13548506.2019.1634822
|View full text |Cite
|
Sign up to set email alerts
|

Associations between personality traits and adequate home storage of drugs in older patients

Abstract: The objective of this study was to investigate the association between personality traits of older patients and adequate home storage of drugs. Forty-four participating Dutch community pharmacists randomly selected each up to four community-dwelling elderly patients (≥65 years) who were using at least one prescription drug. The Big Five Inventory was used to assess the personality traits -'openness', 'conscientiousness', 'extraversion', 'agreeableness' and 'neuroticism'of patients. An assessment of adequate ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…In this study, we found that people with high agreeableness, high conscientiousness, high neuroticism, and high openness were more likely to regard drug safety as an important consideration. High conscientiousness is a state of caution or vigilance that shows a desire to do something well (Vlieland et al, 2019). Therefore, people with high conscientiousness will pay more attention to the potential risks of OTC drugs to their health and are sensitive to safety.…”
Section: Analysis Of Influencing Factors Of Residents Taking Drug Saf...mentioning
confidence: 99%
“…In this study, we found that people with high agreeableness, high conscientiousness, high neuroticism, and high openness were more likely to regard drug safety as an important consideration. High conscientiousness is a state of caution or vigilance that shows a desire to do something well (Vlieland et al, 2019). Therefore, people with high conscientiousness will pay more attention to the potential risks of OTC drugs to their health and are sensitive to safety.…”
Section: Analysis Of Influencing Factors Of Residents Taking Drug Saf...mentioning
confidence: 99%